2010
DOI: 10.1111/j.1365-2672.2009.04525.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pharynx epithelial cells surface desialylation on receptor-mediated adherence ofStaphylococcus aureus

Abstract: Aims:  To characterize the interaction between cell surface carbohydrates and Staphylococcus aureus. Methods and Results:  In the present study, in vitro adherence of S. aureus to Detroit 562 cells, amount of cell surface desialylation and effect of subterminal monosaccharides on desialylated glycoproteins on adherence was studied with colony counting, HPLC, fluorescence microscopy and fluorometric techniques. According to our findings, S. aureus adherence to pharynx cells was enhanced (40%) after neuraminidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…In contrast to other staphylococcal genome sequences, S. pseudintermedius ED99 and S. delphini 8086 genomes both contain genes encoding a putative sialidase or neuraminidase. The neuraminidase modification of host sugars may contribute to host colonization by providing a carbon source for growth, contributing to biofilm formation, or by enhancing adherence by exposing receptors on the host cell (Sakarya et al, 2010). Overall, the SIG species share a large number of toxins and exoenzymes reflecting their recent common ancestry and possibly their common skin niche.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to other staphylococcal genome sequences, S. pseudintermedius ED99 and S. delphini 8086 genomes both contain genes encoding a putative sialidase or neuraminidase. The neuraminidase modification of host sugars may contribute to host colonization by providing a carbon source for growth, contributing to biofilm formation, or by enhancing adherence by exposing receptors on the host cell (Sakarya et al, 2010). Overall, the SIG species share a large number of toxins and exoenzymes reflecting their recent common ancestry and possibly their common skin niche.…”
Section: Resultsmentioning
confidence: 99%
“…The nanB gene for sialidase may contribute to host colonization by providing a carbon source for growth, contributing to biofilm formation, or by enhancing adherence by exposing receptors on the host cell (69). Sialidase enzymes help regulate sialic acid on cell surfaces, which are important determinants of eukaryotic cell-cell interactions (71). Perhaps this virulence gene has played a role in the success of this ST.…”
Section: Discussionmentioning
confidence: 99%
“…The fluctuating glucose levels occurring in the nasal cavity implies that S. aureus has to resort to other carbon sources, which led us to examine how S. aureus sustains NO stress when utilizing other hexoses available in the nasal niche (King, 2010; Krismer et al, 2014; Blanchette et al, 2016). In particular, galactose is important for the colonization of S. aureus , as studies have shown that: (i) S. aureus binds human nasal galactose rich mucins during colonization (Shuter et al, 1996); (ii) S. aureus binds galactose molecules in host glycoproteins (Sakarya et al, 2010); (iii) the S. aureus tagatose 6-phosphate pathway is essential for the catabolism of lactose/galactose, which are sugars present in milk and derivative products (Miallau et al, 2007); and (iv) the malfunctioning of the S. aureus tagatose 6-phosphate pathway leads to accumulation of the dietary D -galactose causing bacterial cell death (Miallau et al, 2007). While in many bacteria, galactose is predominantly metabolized through the Leloir pathway, in S. aureus the galactose breakdown occurs through the tagatose 6-phosphate pathway.…”
Section: Introductionmentioning
confidence: 99%